Students’ Mathematical Abstraction in Constructing Quadrilateral Concepts: A Learning Style Perspective - Widi Yanti; Rita Lefrida; Sutji Rochaminah; Mubarik Mubarik (PRISMA, 2026)
Mathematical abstraction is an important aspect in mathematics learning, especially in helping students form and understand geometric concepts such as quadrilaterals. However, in practice, students' mathematical abstraction process does not always occur uniformly. This is due to differences in individual characteristics, one of which is learning style. Therefore, this study aims to describe the profile of students' mathematical abstraction in forming the concept of quadrilaterals in terms of learning style. This study uses a qualitative approach with a descriptive type. The research subjects consisted of three seventh-grade junior high school students with visual, auditory, and kinesthetic learning styles. Data were collected through a learning style questionnaire, mathematical abstraction tasks on quadrilaterals, and interviews. Data analysis used data condensation, data display, and conclusion drawing and verification. The results of the study showed that students' mathematical abstraction processes differed in each learning style. Visual students were able to go through all aspects of mathematical abstraction (recognizing, building-with, constructing, and consolidation) gradually by utilizing visual representations. Auditory students also achieved all aspects by relying on verbal understanding, although the constructing and consolidation aspects were not systematically arranged. Meanwhile, kinesthetic students rely more on concrete experiences and physical activity in recognizing and consolidating. Therefore, it can be concluded that learning styles determine how students carry out the mathematical abstraction process in forming the concept of quadrilaterals, so this needs to be taken into consideration when designing mathematics learning. Keywords: Mathematical Abstraction; Quadrilaterals; Learning Styles